Topical application of a linoleic acid‐ceramide containing moisturizer exhibit therapeutic and preventive benefits for psoriasis vulgaris: a randomized controlled trial. Issue 6 (19th August 2015) - Liu, Min; Li, Xia; Chen, Xiao‐Ying; Xue, Feng; Zheng, Jie
ABSTRACT: Psoriasis is a chronic skin inflammatory disorder with frequent relapse. Ceramides and their key enzymes are deficient in the lesions, resulting in impaired epidermal permeability barrier, which correlates with disease severity. We evaluated the efficacy of linoleic acid‐ceramide moisturizer (LA‐Cer) as an adjunctive and preventive therapy for psoriasis vulgaris. 106 patients were randomized into two groups. The control group (C1 ) received Mometasone Furoate 0.1% Cream ( MF ) while the treatment group (T1 ) was given 0.1% MF in combination with LA‐Cer moisturizer. Psoriasis Area and Severity Index (PASI), pruritus, capacitance (CAP), and transepidermal water loss (TEWL) of normal skin and lesion were evaluated at Week 0, 2, 4, 8. Subsequently, T1 patients were randomized for another 1 year. LA‐Cer‐group (T2 ) maintained the use of moisturizer while control group (C2 ) discontinued. CAPs, TEWLs, PASI were assessed after 1 year. Primary endpoints (PASI‐50 at Week 8) revealed superiority of LA‐Cer‐MF versus MF, less relapse, and rebound in LA‐Cer‐group than control (C2 ) at Year 1. There were time‐by‐therapy interaction effect on CAPs, lesional TEWL, and PASI. LA‐Cer‐MF induced higher CAP, an earlier reduction of lesional TEWL and PASI than control (C1 ). CAPs, lesional TEWL, and PASI remained stable in LA‐Cer‐group. CAPs, lesional TEWL, and PASI were comparable to the baseline levels in control group (C2 ). Topical LA‐Cer moisturizer can alleviate psoriasis, and could be a valuable approach for the treatment and prevention of psoriasis.